VALIDASI METODE WALKLEY-BLACK UNTUK PENETAPAN C-ORGANIK PADA SAMPEL TANAH MENGGUNAKAN SPEKTOFOTOMETRI UV-VIS - Gladys Carmia Puspita; Subur P. Pasaribu; Aman Sentosa Panggabean (PROSIDING SEMINAR KIMIA, 2025)
The determination of organic carbon (C-organic) content in soil is an important indicator for evaluating soil fertility and environmental quality. This study aims to validate the Walkley–Black method using UV-Vis spectrophotometry for the determination of C-organic content in oil palm plantation soil. The analysis was carried out through the oxidation of organic matter using K₂Cr₂O₇ under acidic conditions, and the reduction of Cr⁶⁺ to Cr³⁺ ions was measured at a wavelength of 587 nm. The validation parameters evaluated included linearity, accuracy, precision, limit of detection (LOD), and limit of quantification (LOQ). The calibration curve produced a linear regression equation of y = 0.0016x + 0.0044 with an R² value of 0.9967, indicating excellent linearity. The accuracy test resulted in an average recovery of 98.09%, which falls within the AOAC acceptance range (80–115%), while the precision test yielded an RSD value of 1.50%, showing high repeatability. The calculated LOD and LOQ values were 1.3669 ppm and 3.3407 ppm, respectively, indicating good sensitivity. Based on these results, the Walkley–Black method using UV-Vis spectrophotometry meets analytical validation criteria and is reliable and efficient for determining organic carbon content in oil palm plantation soil. Keywords: Walkley–Black, C-organic, UV-Vis spectrophotometry, Method validation, Soil